Os posicionamentos do Arcebispo de Cuiabá, D. Francisco de Aquino Corrêa, e a defesa do patriotismo cristão - Marin, Jérri Roberto [UNESP] (Universidade Estadual de Maringa, 2016)
The article analyzes the stands of D. Francisco de Aquino Corrêa, as archbishop of Cuiabá, about Brazil, especially the defense of christian patriotism. As one of the spokesmen of the brazilian church's hierarchy and Apostolic See, he achieved great projection and social influence between the decades of 1910s and 1940s. The empirical references are the speeches and pastoral letters from the period of 1920 to 1940. D. Aquino rethought and defended new forms of participation and appreciation of the Catholic Church as a legitimating force of power, a disciplinary institution of society and as a defender of the national character and the brazilian civilizing process.
The stands of the archbishop of Cuiabá, D. Francisco de Aquino Corrêa, and the defense of Christian patriotism
Keywords: Christian patriotism; D. Francisco de Aquino Corrêa; Neo-Christianity